2023
DOI: 10.1111/peps.12595
|View full text |Cite
|
Sign up to set email alerts
|

Don't just tell me, show me: Impacting perceptions of organizational attraction and fit using activating LGBT diversity signals

Abstract: To appeal to traditionally hard‐to‐reach populations such as the LGBT community, many organizations have made diversity and inclusion a focal point of their recruitment messaging. However, extant research provides little evidence of the effectiveness of this messaging for its intended and non‐intended targets. Building upon a proposed signaling theory typology, we suggest that activating signals—signals that show how diversity and inclusion are actively embodied or “activated” through organizational practices—… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 116 publications
0
4
0
Order By: Relevance
“…Whereas prior studies suggest that evidence-based/activating signals have a greater influence on applicant attraction than expressed/pointing signals do (Bradley et al, 2023;Wilton et al, 2020), work in this area also suggests that organizations that provide both types of signals are viewed most positively by respondents in the target group. For example, Windscheid et al (2016) found pro-female diversity statements only increased women's attraction to the organization when accompanied by evidence that the board of directors was gender-balanced.…”
Section: Signaling Theorymentioning
confidence: 88%
See 3 more Smart Citations
“…Whereas prior studies suggest that evidence-based/activating signals have a greater influence on applicant attraction than expressed/pointing signals do (Bradley et al, 2023;Wilton et al, 2020), work in this area also suggests that organizations that provide both types of signals are viewed most positively by respondents in the target group. For example, Windscheid et al (2016) found pro-female diversity statements only increased women's attraction to the organization when accompanied by evidence that the board of directors was gender-balanced.…”
Section: Signaling Theorymentioning
confidence: 88%
“…Across multiple studies, they found that among Black job seekers, evidence-based cues resulted in significantly higher perceptions of fit, authenticity, and expected work performance and significantly lower perceptions of diversity dishonesty (beliefs that an organization was misleading about the extent to which racial diversity is valued and supported). Bradley et al (2023) relied on a similar rationale, but with different nomenclature-that is, pointing signals that tell a candidate that diversity is valued, versus activating signals that show a candidate that diversity is valued-in their study of recruitment of LGBT candidates.…”
Section: Signaling Theorymentioning
confidence: 99%
See 2 more Smart Citations